Clinical and cost effectiveness of nurse-led self-management interventions for patients with copd in primary care: A systematic review. (June 2017) - Baker, Elizabeth; Fatoye, Francis
Abstract: Background and objective: Chronic obstructive pulmonary disease is increasing in prevalence and constitutes a major cause of morbidity and mortality globally. As well as contributing to a significant decline in health status in many patients, this condition creates a considerable burden on healthcare providers. Self-management interventions are frequently implemented in community settings to limit the impact of chronic obstructive pulmonary disease on everyday life of individuals and to manage pressure on health systems. Nurses are the most likely professional group to provide self-management support. This systematic review aims to evaluate the clinical and cost effectiveness of nurse-led self-management for patients with chronic obstructive pulmonary disease in primary care. Design: A systematic review was conducted to identify randomized controlled studies comparing nurse-led self-management interventions to usual care Data sources: Seven electronic databases, including British Nursing Index, MEDLINE, CINAHL, AMED, EMBASE, Cochrane Library and NHS Economic Evaluation Database, were searched for relevant studies. Review methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist was used to guide the structure of the review. The relevance of citations was assessed based on inclusion criteria, with full texts retrieved as required to reach a decision. Data extraction was performed independently by two reviewers. The Cochrane risk of bias tool was used to undertake a quality review. A narrative summary method was used to describe review findings. Results: Twenty-six articles describing 20 randomised controlled trials were included in the analysis. Self-management interventions were heterogeneous, with a variable number of components, level of support, mode of delivery and length of follow up. The review demonstrated that nurse-led self-management programmes may be associated with reductions in anxiety and unscheduled physician visits and increases in self-efficacy, but definitive conclusions could not be reached. Few studies addressed economic outcomes and the diverse perspectives, time frames and settings made comparisons difficult. Evidence on cost-effectiveness was inconclusive. Conclusions: Some nurse-led self-management programmes in this systematic review produced beneficial effects in terms of reducing unscheduled physician visits, lowering patients' anxiety and increasing self-efficacy, but there is insufficient evidence to reach firm conclusions on the clinical or cost-effectiveness of the interventions. Further research should aim to identify the optimal components of these programmes and to identify those patients most likely to benefit. The inclusion of economic analyses in future studies would facilitate decisions by policy makers on the implementation of self-management interventions.